2005
DOI: 10.1002/cncr.20810
|View full text |Cite
|
Sign up to set email alerts
|

Predicting psychological morbidity in Chinese women after surgery for breast carcinoma

Abstract: BACKGROUND Between 30% and 70% of western women experience psychological morbidity after undergoing surgery for breast carcinoma; however, the rates and risk factors among Chinese women are unknown. Identifying at‐risk women enables preventive intervention. METHODS Among 430 Chinese women who were approached within 1 week after undergoing surgery for early‐stage breast carcinoma (baseline), 405 women (94%) completed measures of self‐efficacy and psychological morbidity (the Chinese Health Questionnaire 12‐item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…In our study, a significant difference was found in positive expression rate of CCND1 between different tumors except for tumors of esophagus (c 2 = 7.500, P = 0.058) and colon (c 2 = 7.273, P = 0.064). These results agree with the conclusions of other studies [23,24] . The expression of CCND1 plays an important role in the early staging of carcinogenesis in Caucasian females with breast carcinoma.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our study, a significant difference was found in positive expression rate of CCND1 between different tumors except for tumors of esophagus (c 2 = 7.500, P = 0.058) and colon (c 2 = 7.273, P = 0.064). These results agree with the conclusions of other studies [23,24] . The expression of CCND1 plays an important role in the early staging of carcinogenesis in Caucasian females with breast carcinoma.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study indicated that even a brief reactivation of endogenous Tp53 in Tp53-deficient tumors can lead to a complete tumor regression [22] . At present, the expression of CCND1 has been investigated in several differences tumors, showing that patients with positive expression of CCND1 usually have a poor prognosis compared to those with negative expression of CCND1 in lung cancer, head and neck squamous cell carcinoma, and bladder cancer [23] . Although positive expression of CCND1 can serve as a poor prognostic factor or is associated with a worse prognosis, the expression of CCND1 is not correlated with the prognosis of cancer patients [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, breast cancer caused 502,000 deaths worldwide (7% of cancer mortality; almost 1% of all mortality) (2). During recent years, the incidence rate of breast carcinoma has gradually increased in Asia and has become the second most common malignant tumor of Chinese women, with the number of new cases currently at approximately 60,000 in China annually (3). Ductal breast cancer is the most common type of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the second leading cause of mortality in women (Dunning et al, 1999). In Asia, the prevalence of breast cancer has been increasing during the recent years (Lam et al, 2005). Moreover, the mean age of onset of breast cancer is reduced in Iran (Golmohammadi and Pejhan, 2012).…”
Section: Introductionmentioning
confidence: 99%